Fructan Biosynthetic and Breakdown Enzymes in Dicots Evolved From Different Invertases. Expression of Fructan Genes Throughout Chicory Development - Wim Van den Ende; An Michiels; Joke De Roover; Andrea Van Laere (The Scientific World Journal)
Fructans are fructose-based oligo- and polymers that serve as reserve carbohydrates in many plant species. The biochemistry of fructan biosynthesis in dicots has been resolved, and the respective cDNAs have been cloned. Recent progress has now succeeded in elucidating the biochemistry and molecular biology of fructan biodegradation in chicory, an economically important species used for commercial inulin extraction. Unlike fructan biosynthetic genes that originated from vacuolar-type invertase, fructan exohydrolases (FEHs) seem to have evolved from a cell-wall invertase ancestor gene that later obtained a low iso-electric point and a vacuolar targeting signal. Expression analysis reveals that fructan enzymes are controlled mainly at the transcriptional level. Using chicory as a model system, northern analysis was consistent with enzymatic activity measurements and observed carbohydrate changes throughout its development.